Behavioral Counseling with Engineering Modeling and Technique Token Economy to improve Confidence - Sari, Km. Shintia Agustini Purnama; N. Dantes, N. Dantes; Arum MWP, Dewi (Bisma The Journal of Counseling, 2017)
This study aims to determine the effect of behavioral counseling with modeling techniques and token economy techniques to improve self-confidence in learning in students of class X SMA N 1 Singaraja. This research type is quasi experiment with research design noequivalent pretest-posttest control group design. In this study using purposive sampling technique. Testing Hypothesis 1, found t count = 11.37. The results should be consulted with t table. Based on dk = n-1 = 12-1 = 11 at the level of significance 0.05 obtained t table = 2.201. This means t arithmetic 11.37> t table 2.201. Testing Hypothesis 2 found t arithmetic = 11.48. The results should be consulted with t table. Based on dk = n-1 = 12-1 = 11 at the level of significance 0.05 obtained t table = 2.201. This means t arithmetic 11.48> t table 2.201. Result Hypothesis 3 get coefficient of F count equal to 13,588> with db: 1; 10 = 4,96. If set significance level α = 0.05.